A New Methodology for Estimating Costs and Benefits of Climate Information Services (CIS) among Smallholder Farmers - Timu, Anne (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
One of the main objectives of the Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) program is to facilitate the development and evaluation of tailored climate information services (CIS) for smallholder farmers across SSA. To provide an economic justification for investing in CIS, this briefing note introduces the building blocks of a toolkit to determine costs and benefits of CIS. Understanding these costs and benefits will help design and scale-up economically viable CIS packages and determining the impacts of CIS on smallholder farmers’ livelihoods. Existing cost-benefit analysis methods tend to quantify the net present value (NPV) of future cash flows, which neglects benefits that are not directly valued in monetary terms such as more stable incomes, improved consumption smoothing when exposed to climate shocks, changes in time use, and the intra-household distribution of the costs and benefits. We present an expected utility framework to quantify and aggregate such benefits for more comprehensive cost-benefit analyses of CIS packages. The toolkit is still a work in progress and the authors welcome feedback and comments from readers and potential users.